Automatic Drain System in Seawater Aquarium with Fuzzy Logic Method - Adin, Nur; Nuha, Hilal Hudan (STMIK Budi Darma, 2020)
In seawater aquariums, seawater quality plays a very important role for the survival of the biota in it. There are measurement parameters that determine the quality of the seawater fit to be inhabited by seawater ornamental fish such as clown fish. Measurement parameters are such as temperature, salinity, dissolved oxygen content (DO), pH, ammonia, nitrite, and nitrate. Current technological developments make it possible to create a system that automatically conducts seawater drainage in a seawater aquarium so that the quality of the seawater remains in accordance with its measurement parameters and is fit for habitation by seawater ornamental fish such as clown fish. In this study the measurement parameters that become the reference are the temperature, pH (acidity) values obtained from the temperature sensor and the pH sensor. For normal temperatures, if the temperature is in the range of 24°C to 28°C, while for the ideal temperature is in the range of 25-27°C. For an appropriate pH in a saltwater aquarium is 7.5-8.5 with an ideal pH of 8.2. From the results of measurements made by these sensors, the value will be processed using the fuzzy logic method, then the condition of sea water quality in the aquarium can be seen from the smartphone, and when the measurement results show an inappropriate value, the system will automatically drain the water